State power 2.0 authoritarian entrenchment and political engagement worldwide - Hussain, Muzammil M.; Howard, Philip N. (Ashgate Pub., 2013)
What causes state-powers to block internet access, disable digital networks or even shut off internet access? How is it done, what is the impact and how do dissidents attempt to fight back? In this timely and accessible volume a collection of high profile, international scholars answer these key questions using cases from Israel, Iran, Russia.